Time of developing surgical site infections and its association with patient and procedure characteristics - Saad A. Almohrij (Journal of Infection and Public Health)
Background: Understanding the timeframe and risk of developing surgical site infection (SSI) is essential for effective prevention and management strategies. The objective was to examine the post-operative duration before developing SSI and to characterize their patient and procedure characteristics. Methods: Prospective SSI surveillance was conducted on 15 operative procedures between 2014 and 2023 in a tertiary-care hospital system. The duration before developing SSI was divided into two groups; early-onset (<median) and late-onset (≥ median) SSIs. Results: A total 322 SSI events were included. Approximately 76.7 % of them were superficial, 13.0 % deep, and 10.2 % organ. The majority were detected after discharge (66.6 %) and were laboratory-confirmed (64.6 %). The majority of procedures with SSI were inpatient procedures (96.9 %) and had risk index category of one (70.2 %). The median and mode (most frequent) duration before developing SSI were 15 and 10 days, respectively. Approximately 92.5 % and 98.8 % of SSI were detected within first 30 or 60 days, respectively. After adjusting for all variables that were associated with the duration before developing SSI in univariate analysis, early-onset SSI was significantly associated with female gender (odds ratio [OR] = 2.29, 95 % confidence 1.18–4.45, p = 0.015) and detection before hospital discharge (OR = 8.06, 95 % confidence 3.83–16.93, p < 0.001) but not coronary artery bypass graft (OR = 0.27, 95 % confidence 0.15–0.51, p < 0.001). Conclusions: As most of SSI are detected after discharge, the findings underscore the importance of post-discharge surveillance that can be considered as a quality indicator for surveillance. Reducing the SSI follow-up durations from 90 days to 60 days, wouldn’t make much difference.